OPTIMIZING PERFORMANCE OF MULTIUSER MIMO OFDM SYSTEMS WITH FEEDBACK DELAY, ERROR, AND INTER-CARRIER INTERFERENCE (ICI) - Arunabh Kumar 1, Dr. Anurag Shrivastava 2, Dr. Sanjay Kumar Suman 3 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The availability of Channel State Information (CSI) at the transmitter in Multiuser Multiple-Input Multiple-Output (MU-MIMO) systems is an extremely important factor in determining whether or not the system will perform at its absolute best. Typically, this is accomplished through the use of feedback systems. Within the context of orthogonal frequency division multiplexing (OFDM), this study analyzes how the availability of CSI and feedback faults affect the performance of broadcast multiuser MIMO systems. In the analysis, channel-dependent scheduling, beamforming techniques, and the impacts of feedback latency and error are all taken into account. When determining the ergodic capacity and the Bit Error Rate (BER), various elements, including the noise variance, the modulation order, the number of users, and the number of antennas, are taken into consideration. The findings highlight the importance of CSI as well as the adverse impact that feedback errors and inter-carrier interference (ICI) have on the performance of the system. These findings provide useful insights that may be applied to the design and optimization of multiuser MIMO OFDM systems in real-world circumstances.